2020
DOI: 10.1111/ppl.13114
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and quantitative trait loci analyses of the anthocyanins and catechins of Camellia sinensis cultivar ‘Ziyan’ with dark‐purple leaves

Abstract: Owing to the potential health benefits, anthocyanin-rich teas (Camellia sinensis) have attracted interest over the past decade. Previously, we developed the cultivar 'Ziyan,' which has dark-purple leaves because of the accumulation of a high amount of anthocyanins. In this study, we performed a genetic analysis of this anthocyanin-rich tea cultivar and 176 of its naturally pollinated offspring. For two consecutive years, we quantified the anthocyanins and catechins of 'Ziyan' and the offspring population. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…We speculate that the total illumination radiation, instead of light period, is important for anthocyanin accumulation. The increase in catechins may also lead to the decrease in anthocyanins as they share the upstream biosynthetic pathway (Tan et al, 2020). However, we failed to find previous research that indicated that applying extra weak light during the night decreased the content of anthocyanins.…”
Section: Impacts On the Important Biochemical Componentscontrasting
confidence: 70%
See 1 more Smart Citation
“…We speculate that the total illumination radiation, instead of light period, is important for anthocyanin accumulation. The increase in catechins may also lead to the decrease in anthocyanins as they share the upstream biosynthetic pathway (Tan et al, 2020). However, we failed to find previous research that indicated that applying extra weak light during the night decreased the content of anthocyanins.…”
Section: Impacts On the Important Biochemical Componentscontrasting
confidence: 70%
“…The signal was detected by using an Agilent VWD at 520 nm. The contents of catechins and caffeine were determined by HPLC (Agilent 1260), as described by Tan et al (2020). A Phenomenex (Torrance, CA, USA) phenyl-hexyl column was used.…”
Section: Measurement Of Biochemical Componentsmentioning
confidence: 99%
“…According to the method described by China National Standard GB/T8305-2013, GB/T8313-2008 and GB/T8314-2013, water extract content (WE), tea polyphenols (TPs) and amino acid (AA) in tea samples were quantified, respectively. Furthermore, the levels of catechin monomers and caffeine (Caf) were determined following GB/T 8313–2018 with some modifications by Tan et al (2021) , while water-soluble sugar (SS) were detected by the method of Zou (2014) . The contents of theaflavin (TF), thearubigin (TR) and theabrownin (TB) were, respectively, measured using spectrophotometric methods ( Huang, 1997 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tea varieties possessing purple leaves represent another emerging popular tea type [19]. Compared to traditional green-leaf cultivars, purple-leaf tea is rich in purple-colored bioactive anthocyanins [20][21][22]. Anthocyanins are polyphenols and possess powerful antioxidative and anti-inflammatory capacities [23].…”
Section: Introductionmentioning
confidence: 99%